The Number of Immune Defence and Counter-Defence Systems Sustained in the Arms Race Between Prokaryotes and Viruses - Ispolatov, y (Nature Research, 2025)
Prokaryotes have evolved various mechanisms to counter viruses, which in their turn developed numerous strategies to avoid defences of the hosts. Dozens of these defence and counter-defence mechanisms have recently been discovered, yet a given virus or its host possesses only several of such systems. Here, we present numerical and theoretical arguments for the existence of the maximal number of ecologically and evolutionary sustainable defence and counter-defence systems maintained by both sides at any time of the never-ending evolutionary arms race. We find that the number of such systems is of the order of 10 for a broad range of assumptions about the costs and benefits of defence and counter-defence mechanisms and their specificity. This limit appears as a result of a compromise between the metabolic and autoimmune costs of adding a new layer of defence and the benefits it conveys. © The Author(s) 2025.